Homologous recombination is involved in the diversity of replacement flexible genomic islands in aquatic prokaryotes - López-Pérez, Mario; Martin-Cuadrado, Ana-Belen; Rodriguez-Valera, Francisco (Frontiers in Genetics, 2014)
Different strains of the same prokaryotic species, even very similar ones, vary in large regions of their genomes. This flexible genome represents a huge reservoir of diversity that allows prokaryotes to exploit their environment efficiently. Most of the flexible genome is concentrated in genomic islands, some of which are present in all the strains and coding for similar functions but containing different genes. These replacement genomic islands are typically involved in exposed cellular structures, and their diversity has been connected to their recognition as targets by prokaryotic viruses (phages). We have compared genomes of closely related aquatic microbes from different origins and found examples of recent replacement of some of these flexible genomic islands. In all cases, that include Gram positive and negative bacteria and one archaeon, the replaced regions boundaries contain tell-tale peaks of increased, mostly synonymous, nucleotide substitutions. They tended to be sharper at the boundary closest to the origin of replication of the island. We will present the hypothesis that replacement flexible genomic islands are often exchanged by homologous recombination between different clonal frames. These recombination events are possibly selected due to the immediate reward provided by a change in the phage sensitivity spectrum.